Pengaruh Current Ratio, Debt to Asset Ratio, dan Total Asset Turn Over terhadap Net Profit Margin: Studi Empiris pada Perusahaan Sub Sektor Retail yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Hermawan Wihardja; Rachmat Arif (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This study aims to determine the effect of Current Ratio, Debt to Asset Ratio and Total Asset Turn Over on Net Profit Margin. The data used in this study is secondary data with a population of retail sub-sector companies listed on the Indonesia Stock Exchange with the observation year 2019 - 2022, totaling 31 companies. The sampling technique used in this study was purposive sampling method with data analysis using multiple linear regression methods and using the Statistical Package for the Social Sciences (SPSS) version 22 program and Microsoft Excel for Windows 2019. The results of this study indicate that Current Ratio, Debt to Asset Ratio and Total Asset Turn Over affected Net Profit Margin with a coefficient of determination (R2) of 83.3% and the rest is influenced by other variables not studied in this study.